Flood Management Solutions at Panca Budi School in Medan - Dian Syahputra; Abdi Sugiarto (Yayasan Sinergi Multidimensi Kreatif, 2024)
Flooding is one of the problems that often occurs in the Panca Budi School in Medan, especially during the rainy season. This problem is caused by poor drainage systems, low soil absorption due to reduced green open space, and suboptimal waste management. This study aims to analyze the factors that cause flooding in the school environment and design solutions based on a sustainable approach to overcome these problems. The research method used is qualitative descriptive with data collection techniques through observation, interviews, and literature studies. The results showed that high rainfall intensity, inadequate drainage system, and low environmental awareness were the main causes of flooding at Panca Budi School in Medan. The solutions offered include improving the drainage system through the construction of larger and closed channels, the implementation of green infrastructure such as infiltration wells and bio-retention parks, rainwater management with rainwater harvesting systems, and education and involvement of the school community to maintain environmental cleanliness. The implementation of this solution also emphasizes sustainability by ensuring regular evaluation of the effectiveness of the measures that have been implemented. This research is expected to be a guide in overcoming flood problems in the school environment, creating safe and comfortable learning spaces, and contributing to better environmental management.